Smoking's impact on pocket closure after nonsurgical periodontal treatment in relation to bleeding on probing - Yilmaz, Mustafa; Ujanen, Aleksandra; Suominen, Auli; Demir, Esra; Gürsoy, Ulvi Kahraman (QUINTESSENCE PUBLISHING CO INC, 2026)
Objectives: The aim was to investigate the impact of smoking on pocket closure at 6 months after treatment of severe periodontitis, in relation to residual clinical inflammation.
Method and materials: The clinical records of deep pockets (probing depth >= 6 mm, n=984) in 46 individuals with periodontitis were analyzed. Following baseline clinical assessments (Plaque Index, probing depth, clinical attachment level, and bleeding on probing), nonsurgical periodontal treatment was performed. Clinical assessments were repeated at 2 and 24 weeks after periodontal therapy. A logistic regression model using general-errors was performed to investigate potential associations between bleeding on probing , pocket closure at posttreatment 24 weeks.
Results: Absence of bleeding at 2 weeks after nonsurgical treatment related to pocket closure after 6 months. Pockets that do not bleed either at baseline or at 2weeks (OR= 2.7; P<.005) and pockets of nonsmokers (OR= 6.32; P<.001) and females (OR= 1.79; P=.022) associated with pocket closure at 6 months.
Conclusion: Pocket closure is associated with being a nonsmoker and the absence of inflammation after nonsurgical periodontal treatment, which indicates the importance of smoking cessation and inflammation control in achieving optimal clinical outcomes. (Quintessence Int 2024;55:780-789; doi: 10.3290/j.qi.b5716359)